2011
DOI: 10.1038/ismej.2011.164
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic oxidation of methane at different temperature regimes in Guaymas Basin hydrothermal sediments

Abstract: Anaerobic oxidation of methane (AOM) was investigated in hydrothermal sediments of Guaymas Basin based on d 13 C signatures of CH 4 , dissolved inorganic carbon and porewater concentration profiles of CH 4 and sulfate. Cool, warm and hot in-situ temperature regimes (15-20 1C, 30-35 1C and 70-95 1C) were selected from hydrothermal locations in Guaymas Basin to compare AOM geochemistry and 16S ribosomal RNA (rRNA), mcrA and dsrAB genes of the microbial communities. 16S rRNA gene clone libraries from the cool a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

33
155
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(188 citation statements)
references
References 43 publications
33
155
0
Order By: Relevance
“…This suggests that seafloor inputs of hydrocarbons have had a major and geographically widespread impact on the types and activities of microorganisms in the deep Gulf of California, leading to microbial communities with an enormous capacity for consumption of seafloor-derived methane. These results are consistent with prevalent diffusive seepage of methane from sediments, potentially including low-temperature surface sediments away from active hydrothermal venting (Lizarralde et al, 2011;Biddle et al, 2012). Interestingly, we recovered abundant transcript sequences encoding methane monooxygenases that were 100% identical to methanotrophs recently reported from the Deepwater Horizon oil spill (Kessler et al, 2011).…”
Section: Discussionsupporting
confidence: 88%
“…This suggests that seafloor inputs of hydrocarbons have had a major and geographically widespread impact on the types and activities of microorganisms in the deep Gulf of California, leading to microbial communities with an enormous capacity for consumption of seafloor-derived methane. These results are consistent with prevalent diffusive seepage of methane from sediments, potentially including low-temperature surface sediments away from active hydrothermal venting (Lizarralde et al, 2011;Biddle et al, 2012). Interestingly, we recovered abundant transcript sequences encoding methane monooxygenases that were 100% identical to methanotrophs recently reported from the Deepwater Horizon oil spill (Kessler et al, 2011).…”
Section: Discussionsupporting
confidence: 88%
“…6). Only relatively low SR and AOM rates were measured at the vents, as compared to other methane-rich hydrothermal vents and seeps that are not impacted by CO 2 leakage (Biddle et al, 2011;Felden et al, 2010).…”
Section: Discussionmentioning
confidence: 81%
“…Microsensors for O 2 , H 2 S, and pH were made and used as described previously (de Beer et al, 1997;Jeroschewski et al, 1996;Revsbech, 1989). The tip diameters were approximately 20 µm, the response time (t 90 ) less than 3 s. A temperature sensor was used (Pt100, UST Umweltsensortechnik GmbH, Thüringen, Germany), with a length of 18 cm, a shaft and tip diameter of 3 mm and length of sensing element of 1 cm and a response time of ∼ 5 s. Microsensors for redox potential (ORP) were made from Pt wire of 50 µm diameter, fused in a glass capillary, leaving a length of 100 µm Pt exposed as sensing surface.…”
Section: Microprofilingmentioning
confidence: 99%
“…Molecular ecological studies have indicated that the ANME-1 populations occur in deeper, more reductive and more sulfate-depleted habitats than the ANME-2 populations (Knittel et al, 2005;Krüger et al, 2008;Nunoura et al, 2008;Rossel et al, 2011;Yanagawa et al, 2011). Furthermore, the potentially thermophilic ANME-1 group has been recognized as a key component in certain hydrothermal ecosystems, such as Guaymas Basin and Juan de Fuca Ridge (Biddle et al, 2012;Lever et al, 2013;Merkel et al, 2013). This mcrA group of thermophilic ANME-1 is defined as Hydrothermal ANME-1 Cluster II (Lever et al, 2013) (alternatively classified as mcrA-Guaymas (Biddle et al, 2012) or ANME-1GBa (Merkel et al, 2013)).…”
Section: Microbial Functions Of Methanogenesis and Aommentioning
confidence: 99%
“…Furthermore, the potentially thermophilic ANME-1 group has been recognized as a key component in certain hydrothermal ecosystems, such as Guaymas Basin and Juan de Fuca Ridge (Biddle et al, 2012;Lever et al, 2013;Merkel et al, 2013). This mcrA group of thermophilic ANME-1 is defined as Hydrothermal ANME-1 Cluster II (Lever et al, 2013) (alternatively classified as mcrA-Guaymas (Biddle et al, 2012) or ANME-1GBa (Merkel et al, 2013)). The optimal growth temperatures of the thermophilic ANME-1 in the Guaymas site have been estimated to be above 70°C (Merkel et al, 2013).…”
Section: Microbial Functions Of Methanogenesis and Aommentioning
confidence: 99%